Patient perceived quality of cirrhosis care- adjunctive nurse-based care versus standard medical care: a pragmatic multicentre randomised controlled study - Maria Hjorth; Anncarin Svanberg; Riccardo LoMartire; Elenor Kaminsky; Fredrik Rorsman (BMC, 2024)
Abstract Background Cirrhosis treatment implies prevention and alleviation of serious disease events. Healthcare providers may, however, fail to meet patients' expectations of collaboration and specific needs of information and support. Individualised nursing care could meet patients' needs. The aim was thus to measure patient-perceived quality of care after adjunctive registered nurse-based intervention Quality Liver Nursing Care Model (QLiNCaM) compared with standard medical care. Methods This pragmatic multicentre study consecutively randomised patients to either adjunctive registered nurse-based care, or standard medical care for 24 months (ClinicalTrials.gov NCT02957253). Patients were allocated to either group at an equal ratio, at six Swedish outpatient clinics during 2016-2022. Using the questionnaire 'Quality of care from the patient's perspective', patients rated their perceived lack of quality for the adjunctive registered nurse-based intervention compared with the control group at 12 and 24 months, respectively. Results In total, 167 patients were recruited. Seven out of 22 items in the questionnaire supported the finding that 'lacking quality' decreased with adjunctive registered nurse-based care (p < 0.05) at 12 months follow-up; however, these differences could not be established at 24 months. Conclusion Additional structured registered nurse-based visits in the cirrhosis outpatient team provided support for improved patient-perceived quality of care during the first 12 months. Registered nurses increase patient involvement and present easy access to cirrhosis outpatient care. Patients express appreciation for personalised information. This study reinforces registered nurses' role in the outpatient cirrhosis team, optimising patient care in compensated and decompensated cirrhosis. Trial registration Registered at Clinical Trials 18th of October 2016, [ https://www.clinicaltrials.gov ], registration number: NCT02957253.